Estimation of daily vertical solar irradiation by the use of meteorological data - Mourad Benziane; Mouloud Ayad; Kamel Saoudi; Mohamed Rezki (Institute of Advanced Engineering and Science, 2019)
Energy has been recognized as one of the most inputs for social and economic improvement and a clean energy is a challenge in the future. Therefore, renewable energy has become one of the most popular sources of energy. The solar energy, is one of this renewable energy, has the most propriety which is the durability. Due to its geographical location, Algeria has one of the world’s most important gas reserves, and has in addition one of the highest solar reservoirs in the world. Solar irradiation is an essential parameter for many applications such as the design and performance of renewable energy systems, but this is not always available, especially in remote locations. The prediction of solar irradiation values is often the only practical way to acquire these data. The objective of this work is to develop a model for the prediction of the Vertical Solar Irradiation (VSI) based on real meteorological data. This model is based on the Artificial Neural Networks (ANN).